2018
DOI: 10.1111/hepr.13041
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of virtual touch quantification for staging liver fibrosis in patients with hepatitis C, and factors affecting liver stiffness measurement failure compared with liver biopsy

Abstract: Virtual touch quantification is a non-invasive, simple method that is more accurate for staging liver fibrosis than the FIB-4 index and APRI. However, when the SCD is longer than 17.5 mm, there may be measurement failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 69 publications
0
8
1
Order By: Relevance
“…These results indicate that the median liver stiffness generally increased with the severity of fibrosis (F0-F4), but between immediately adjacent stages there were no significant differences, except for F2 versus F3. This observation suggests that SWV measurements cannot differentiate fine differences between different fibrosis stages, which is similar to the results presented by Jain et al [23], but is inconsistent with the study by Zheng et al [5], who found patients in each fibrosis stage to have significantly higher median liver stiffness than those with less fibrosis, as well as similar findings reported by Ozkan et al [12] and Tsukano et al [24]. The SWV of the liver showed no significant difference between patients with a normal liver and inactive HBV carriers, suggesting that if inactive HBV carriers do not suffer continuous or repeated active inflammation, their livers are likely to generate slight stiffness (with minimal to no fibrosis).…”
Section: Discussioncontrasting
confidence: 74%
“…These results indicate that the median liver stiffness generally increased with the severity of fibrosis (F0-F4), but between immediately adjacent stages there were no significant differences, except for F2 versus F3. This observation suggests that SWV measurements cannot differentiate fine differences between different fibrosis stages, which is similar to the results presented by Jain et al [23], but is inconsistent with the study by Zheng et al [5], who found patients in each fibrosis stage to have significantly higher median liver stiffness than those with less fibrosis, as well as similar findings reported by Ozkan et al [12] and Tsukano et al [24]. The SWV of the liver showed no significant difference between patients with a normal liver and inactive HBV carriers, suggesting that if inactive HBV carriers do not suffer continuous or repeated active inflammation, their livers are likely to generate slight stiffness (with minimal to no fibrosis).…”
Section: Discussioncontrasting
confidence: 74%
“…That is, the CHC cohort manifested higher age compared with the CHB cohort (median age 49 years in the CHB cohort and 63 years in the CHC cohort; P < 0.0001). The Fib‐4 index includes age and Japanese CHC patients are aging . Individual cut‐off values of LF markers in each etiology of CLD for the severity of LF should thus be in use in the clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has focused on the evaluation of non‐invasive assessment methods for the severity of LF. Currently, one of the major ultrasound‐based assessment methods for LF using shear wave velocity is acoustic radiation force impulse (ARFI) . Several meta‐analyses and systematic reviews confirmed clinical utility of ARFI for the evaluation of the severity of LF .…”
Section: Introductionmentioning
confidence: 99%
“…Virtual Touch™ Quantification is a new software which represents an application of acoustic radiation force impulse technology [18] that can be used to diagnose and monitor the evolution of liver fibrosis [19]. It can more accurately estimate liver fibrosis versus aspartate aminotransferase-to-platelet ratio index (APRI) and fibrosis-4 index.…”
Section: Attempts To Assess Liver Fibrosis By Imaging Meansmentioning
confidence: 99%
“…It can more accurately estimate liver fibrosis versus aspartate aminotransferase-to-platelet ratio index (APRI) and fibrosis-4 index. Discrepancies between the pathological fibrosis stage and the liver stiffness values estimated by virtual touch quantification may exist when the distance between the skin and the liver capsule is over 17.5 mm [18]. It has slightly higher sensitivity and specificity on significant fibrosis assessment versus transient elastography, according to the results of a metaanalysis that included patients with chronic hepatitis B or C virus infection.…”
Section: Attempts To Assess Liver Fibrosis By Imaging Meansmentioning
confidence: 99%